2009
DOI: 10.1159/000218111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Age-at-Onset for Cardiovascular Risk Factors in a Brazilian Family Study

Abstract: Background/Aims: Statistical analysis of age-at-onset involving family data is particularly complicated because there is a correlation pattern that needs to be modeled and also because there are measurements that are censored. In this paper, our main purpose was to evaluate the effect of genetic and shared family environmental factors on age-at-onset of three cardiovascular risk factors: hypertension, diabetes and high cholesterol. Methods: The mixed-effects Cox model proposed by Pankratz et al. [2005] was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…From the polygenic model, we obtained an estimate of polygenic variance component equal to 0.21 for males, with a 95% confidence interval of 0.01 - 0.54. Considering that polygenic variance estimates can be interpreted as measures of familial aggregation [18], this result suggests an intermediate degree of familial aggregation associated with the age-at-onset of regular cigarette use and shows that the individual relative risk of cigarette use due to polygenic effects among males are on average exp(√0.21) = 1.58. Among females, we observed a moderate polygenic variance estimate of 0.40 (95% CI, 0.11 - 0.78) indicating a higher level of familial aggregation compared to males and a risk of cigarette use which may be 88% (exp(√0.40) = 1.88) higher than the average risk of this sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the polygenic model, we obtained an estimate of polygenic variance component equal to 0.21 for males, with a 95% confidence interval of 0.01 - 0.54. Considering that polygenic variance estimates can be interpreted as measures of familial aggregation [18], this result suggests an intermediate degree of familial aggregation associated with the age-at-onset of regular cigarette use and shows that the individual relative risk of cigarette use due to polygenic effects among males are on average exp(√0.21) = 1.58. Among females, we observed a moderate polygenic variance estimate of 0.40 (95% CI, 0.11 - 0.78) indicating a higher level of familial aggregation compared to males and a risk of cigarette use which may be 88% (exp(√0.40) = 1.88) higher than the average risk of this sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, the variance components estimated may be interpreted as measures of familial aggregation [18]. The relative risk of the smoking behavior that corresponds to the random effect is obtained by exponentiation of the square root of the variance component.…”
Section: Methodsmentioning
confidence: 99%
“…The initial publication 19 determined the extent to which unmeasured genetic factors and measured environmental and lifestyle factors contributed to variation in a large panel of cardiovascular-related traits. Subsequent studies identified that age-at-onset is a useful trait for gene mapping of common complex diseases 21 and reported that heterogeneity in trait variances needs to be accounted for in the design and analyses of trait orientated gene finding studies. 22 Lifestyle factors, including physical activity 23 and smoking 24 have also been a focus of the study.…”
Section: Findings To Datementioning
confidence: 99%
“…This comprehensive model has been extended to include components of the Cox model, random effects, and familial relationship (kinship or identity by descent [IBD] matrix in families) in the Cox model survival analysis. [21][22][23] Kinship IBD matrixes were created, using the genotypic data in kinship software, and Cox model survival analysis was performed on each SNP using the age at diagnosis of PLL and the disease status, whereas the structure of individual random effect was adjusted using the kinship IBD matrixes. Association of the genome-wide SNPs with the disease risk was estimated using the Wald test v 2 for each SNP.…”
Section: Survival Analysismentioning
confidence: 99%